A pre-magnetized NdFeB-particle reinforced magnetorheological elastomer. (20th November 2020) - Xie, Yuanpeng; Qi, Song; Fu, Jie; Tian, Ruixue; Liu, Fenglin; Yu, Miao
Abstract: It is known that the modulus of magnetorheological elastomer (MRE) doping soft magnetic particles only varied monotonously under magnetic fields. It restricts vibration applications of MRE shifting to low frequency. MRE should ensure the bearing capacity of relevant devices, and capable of shifting to low frequency. To this end, MRE was fabricated in this work by incorporating pre-magnetized hard magnetic NdFeB-particles into silicon rubber to achieve bi-directional magnetic control property. Particularly, NdFeB-particles were pre-magnetized before fabrication to enhance the property. Three MRE samples doping NdFeB-particles with different particle sizes and magnetic properties were prepared. The surface magnetic field intensity of samples were recorded by teslameter and the microstructures were observed by SEM and computed tomography. The dynamic mechanical properties were measured by a rheometer under a triangular wave magnetic field. Experimental results indicated that the MRE surface magnetic field intensity on edge was greater than centre. MRE doping pre-magnetized NdFeB-particles with large coercivity could possess greater storage modulus control range and larger loss modulus, which attributes to NdFeB-particles' motion and sensitivity to magnetic field. Thus, MRE reinforced by pre-magnetized hard magnetic particles exhibits excellent potential in bi-directional control property.